2009
DOI: 10.1213/ane.0b013e318192a36b
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Stroke Volume Variations Obtained with Vigileo/FloTrac System to Monitor Fluid Responsiveness in Mechanically Ventilated Patients

Abstract: SVV predicts fluid responsiveness with an acceptable sensitivity and specificity and is also a potential surrogate for continuous monitoring of DeltaPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
103
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(112 citation statements)
references
References 23 publications
1
103
1
3
Order By: Relevance
“…Diagonal segments are produced by ties. (3,4,7). Only one study evaluated the ability of SVV to predict fluid responsiveness in patients undergoing OLV, and they found that SVV measured by the Vigileo-FloTrac system was able to predict fluid responsiveness in patients undergoing surgery with OLV with acceptable levels of sensitivity and specificity.…”
Section: Fluid Responsiveness To Fluid Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Diagonal segments are produced by ties. (3,4,7). Only one study evaluated the ability of SVV to predict fluid responsiveness in patients undergoing OLV, and they found that SVV measured by the Vigileo-FloTrac system was able to predict fluid responsiveness in patients undergoing surgery with OLV with acceptable levels of sensitivity and specificity.…”
Section: Fluid Responsiveness To Fluid Therapymentioning
confidence: 99%
“…In addition, the venous return could be influenced by the mechanical ventilation under chest opening due to the decrease in chest compliance and airway pressure. Previous studies have showed that SVV could predict fluid responsiveness in patients undergoing OLV only when tidal volume is at least 8 mL/kg (13), so in this study tidal volume was set as 8mL/kg, which had been used previously in two-lung ventilation (3,4) or one-lung ventilation (13).…”
Section: Fluid Responsiveness To Fluid Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…From this algorithm, cardiac output (CO) can be calculated, and the percentage of respiratory fluctuations in SV (stroke volume variation: SVV) can be used as an index of fluid responsiveness [7] [8]. Measurement with this system is relatively less invasive and easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the performance of dynamic indicators including SVV is reportedly better than that of static indicators [1][2][3]. For example, SVV can predict fluid responsiveness with both high sensitivity and specificity [4][5][6]. However, since special catheters and expensive machines, such as the FloTrac/Vigileo Monitor® system, must be used to measure SVV, not all facilities can perform this measurement.…”
Section: Introductionmentioning
confidence: 99%